Feeding ecology and food preferences of Cherok Paloh, Pahang horseshoe crab, tachypleus gigas - Md Razak, Mohd Razali; Kassim, Zaleha; Sabuti, Asnor Azrin; Ismail, Ahmad (Penerbit UTM Press, UTM, 2017)
Intensive previous studies on horseshoe crabs feeding ecology were mostly focus on Limulus polyphemus. Their food preference might be different depend on the availability and abundance of feeds in the particular environment. This paper aims to investigate the feeding ecology and food preferences of Cherok Paloh, Pahang Tachypleus gigas. Ten samples of male and female horseshoe crabs, Tachypleus gigas were trapped in fishing net during the incoming high tide and 10 samples of male and female were hand-harvested at the spawning beach during pre and post-mating respectively. Their gut content was analysed by the Electivity Index. Results showed that Tachypleus gigas coming to spawn with full gut content. Echinoderm served as a main food composition in the gut of males (50%) and females (51.94%) during the open sea migration phase. The main composition was substituted by macrophyte (males: 59.51% to 65.15%; females: 36.36% to 58.10%) as they arrived to shore. Based on Electivity Index, male crabs showed positive preference toward polychaete (EI: 0.04) and macrophyte (EI: 0.19) at the spawning site while, the females showed positive preference toward bivalve (EI: 0.46). Further study on feeding ecology is needed in order to improve the population of Tachypleus gigas in Malaysia.